2012
DOI: 10.1136/bmj.e42
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combination treatment with aliskiren and blockers of the renin-angiotensin system on hyperkalaemia and acute kidney injury: systematic review and meta-analysis

Abstract: Objective To examine the safety of using aliskiren combined with agents used to block the renin-angiotensin system.Design Systematic review and meta-analysis of randomised controlled trials.Data sources Medline, Embase, the Cochrane Library, and two trial registries, published up to 7 May 2011.Study selection Published and unpublished randomised controlled trials that compared combined treatment using aliskiren and angiotensin converting enzyme inhibitors or angiotensin receptor blockers with monotherapy using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 31 publications
1
58
1
Order By: Relevance
“…However, it is unclear whether ALK may effectively induce regression of cardiac hypertrophy. Although the combination of ALK with an ACEI or an ARB can synergistically attenuate both 1006 www.nature.com/aps Weng LQ et al Acta Pharmacologica Sinica npg hypertrophy and dysfunction in hypertensive patients [8,9] , a systematic review of randomized, controlled clinical trials has shown that combined therapy is associated with a higher risk of hyperkalemia than monotherapy with an ACEI, an ARB or ALK [10] . In addition, some patients are intolerant of ACEI or ARB, whereas ALK is well tolerated [11] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether ALK may effectively induce regression of cardiac hypertrophy. Although the combination of ALK with an ACEI or an ARB can synergistically attenuate both 1006 www.nature.com/aps Weng LQ et al Acta Pharmacologica Sinica npg hypertrophy and dysfunction in hypertensive patients [8,9] , a systematic review of randomized, controlled clinical trials has shown that combined therapy is associated with a higher risk of hyperkalemia than monotherapy with an ACEI, an ARB or ALK [10] . In addition, some patients are intolerant of ACEI or ARB, whereas ALK is well tolerated [11] .…”
Section: Introductionmentioning
confidence: 99%
“…16 The efficacy of RAAS blockade intensification in an attempt to further reduce residual proteinuria is, however, limited by side effects, such as hyperkalemia and hypotension. 17,18 Adjunctive therapies, which can offer the lowering of residual proteinuria but without these drawbacks, may improve renal and cardiovascular protection.…”
mentioning
confidence: 99%
“…This is important, bearing in mind that trial definitions may not reflect the clinical significance of a side effect. For instance, combination therapy is associated with an increased risk of moderate hyperkalemia (serum potassium >5.5 mEq/l) but not of clinically significant hyperkalemia (serum potassium >6 mEq/l) compared with monotherapy [Harel et al 2012]. Be that as it may, these studies clearly show that combined RAS inhibitors should be avoided in patients with basal normal or nearly normal blood pressure and in those with basal serum potassium concentration greater than 5 mEq/l.…”
Section: Dual Ras Blockadementioning
confidence: 95%